Brahma ekākshara gītā - Yaśobanta Dāsa, b. 1487 (Paramānanda Dāsa : prāptisthāna, Dharmagrantha Shṭora, 1970)
Anthology of poems by five medieval poets, interpreting the mystic syllable Om, sound symbol of Brahman.